Un punto central de la «cuestión antropológica» - Castilla de Cortázar, Blanca (Mercurio Peruano, 2013)
The Letter to Women that Pope Wojtyla wrote 15 years ago, gives a twist to the original proposals on the anthropological question. His message, little known, it requires an extension of the philosophy, that accounts for the “uni-duality native relational” of man, which is revealed already in the book of Genesis.